Quantification of the efficiency of rumen microbial protein synthesis in steers fed green tropical grass - Marthen L. Mullik; Dennis P. Poppi; Stuart R. Mclennan (Indonesian Center for Animal Research and Development (ICARD), 2009)
The rate of rumen microbial crude protein (MCP) supply to the intestines is a crucial element in the current rumen models to predict respond of ruminants to a certain diet. Data from tropical pastures are always below predicted results from the existing rumen models. Thus, quantification of the rumen MCP supply from tropical forage will improve predictive rate under tropical feeding conditions. Four Brahman crossbred steers (457 ± 20.1 kg) were used in a metabolism study. Pangola grass (Digitaria erianthe cv. Steudal) was harvested every morning and fed to the animals soon afterward. Parameters measured were EMPS, intake, fractional passage rates, and rumen ammonia concentration. The EMPS was estimated using purine derivative excretion in urine. Mean crude protein and water soluble carbohydrate was 6.3 and 7.4% of dry matter (DM) respectively. Mean DM intake was 1.6% liveweight. Average rumen ammonia concentration was 69 mg/L whilst rumen passage rates were 7.84 and 6.92%/h for fluid and solids respectively. Mean EMPS was only 72 g MCP/kg digestible organic matters. It is concluded that EMPS in steers consuming green pangola grass was at the level below the minimum recommended value for forage diets adopted in the current feeding standards. Key words: Microbial Protein, Efficiency, Tropical Grass, Cattle